INFLUENCE OF MODELING OF TURBULENCE IN THE FLOW PARAMETERS WITHIN A FOOD OVEN USING THE OPENFOAM® - Verdério Jr, S. A.; Scalon, V. L.; Padilha, A. (Revista de Engenharia Térmica, 2015)
Because of the better flexibility in warming and high production, the continuous furnace tunnel is the better option to the processing of industrialized food products. This study presents a numerical investigation of the effects of RANS turbulence modeling on the main parameters of the air flow inside a continuous oven with indirect heating - velocities, temperatures, streamlines and heat flows by convection and radiation. The geometry and operating conditions used for constructing the model, setting the mesh and initial and boundary conditions were obtained based on values of operating ovens. Modeling consider the hypothesis of air as an ideal gas, incompressible and Newtonian; the equations of continuity, momentum balance and energy in turbulent regime; closing model of two equations κ- ε and radiation model viewFactor. Utilized the free open source software OpenFOAM® for device modeling. The Rayleigh Number of the cavity was used to evaluate the treatment indicated to turbulence. Considering the results obtained, the inclusion of model κ- ε stabilized the velocity fields and temperatures around the average value. In relation to the heat exchanges involved, heat flow by convection on the mat showed negligible compared to the effects of radiation. Due to the discrepancy between the orders of magnitude of convection and radiation, it's difficult the precise evaluation of the first, because small fluctuations in temperature and velocity affect considerably and induce oscillations in their behavior. However, the radiation model attained good approximation the most relevant exchanges, showing a good chance their application in practical cases.